2020
DOI: 10.1055/s-0040-1712099
|View full text |Cite
|
Sign up to set email alerts
|

The State of the Science in Patient-Reported Outcomes for Patients with Lung Cancer

Abstract: Traditionally, clinicians have assumed the primary responsibility for evaluating disease- and treatment-related outcomes. In the past few decades, however, a series of recommendations and standards promulgated by professional societies and regulatory agencies have resulted in increased use of patient-reported outcome (PRO) measures in cancer clinical trials. PROs, such as quality of life (QOL) measures, are important in establishing overall treatment effectiveness in cancer clinical trials, and they can inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 97 publications
(146 reference statements)
0
8
0
Order By: Relevance
“…Lung cancer has become the type of cancer with the highest incidence among all the other types cancers in the world, and it appears to affect more among the young people ( Xiao et al, 2020 ). The existing treatment methods have disadvantages such as poor selectivity, high toxic side-effects and a rapid development of drug resistance ( Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer has become the type of cancer with the highest incidence among all the other types cancers in the world, and it appears to affect more among the young people ( Xiao et al, 2020 ). The existing treatment methods have disadvantages such as poor selectivity, high toxic side-effects and a rapid development of drug resistance ( Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer has become the type of cancer with the highest incidence among all the other types cancers in the world, and it appears to affect more among the young people (Xiao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study may encourage the adoption of QOL as an end point in oncology clinical practice. Xiao et al (23) demonstrated that patient-reported outcomes (including QOL) were a key information source for assessing clinical benefit in cancer trials and for informing clinical decision making. Significant improvements have been made in incorporating patient-reported outcomes in lung cancer trials (23).…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al (23) demonstrated that patient-reported outcomes (including QOL) were a key information source for assessing clinical benefit in cancer trials and for informing clinical decision making. Significant improvements have been made in incorporating patient-reported outcomes in lung cancer trials (23). However, a previous systematic review reported that QOL results were significantly under-reported, with a disappointing decline in the timely inclusion of results in primary publications (24).…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of patientreported outcomes (PROs) has emerged as an important tool to measure patient's perception of their symptoms from lung cancer and their global health status. 1 The regulatory authorities have recognized the relevance of PROs and their importance in supporting labeling claims for drug therapy. The U.S. Food and Drug Administration in its guidance characterizes PROs as any report of a status of a patient's health condition that comes directly from a patient without interpretation of the patient's response by a clinician or anyone else.…”
mentioning
confidence: 99%